QUALITY OF ENGLISH THESIS BY EFL UNDERGRADUATE STUDENTS OF MULAWARMAN UNIVERSITY - Yohansyah Arifin (Center of Language and Cultural Studies, 2014)
This article describes evaluation results of undergraduate theses written by undergraduate EFL students in Universitas Mulawarman Samarinda. Evaluation was based on the quality of description of sections in every chapter of the theses. The presentation of the thesis fulfilled standard presentation of academic report, describing five parts of presentation: introduction, review of related literature, research methodology, findings and discussion, and conclusion and suggestions. However, the substance of each section in the whole thesis was lack of reasoning. In terms of organization and contents, the theses were colored with trivialities in reasoning, coverage of substance to be described in the sections, and details of description. The trivialities of description resulted some crucial points were missing. In addition, language uses and mechanics in the theses were also colored with awkward sentences.